Armed conflict exposure, human capital investments and child labor: evidence from Colombia (2009)
This paper estimates the effect that exposure to armed conflict has on school drop-out and labor decisions of Colombian children between the ages of six and seventeen. We use a duration analysis methodology, complemented by biprobit estimations. Both approaches take into account the possible endogeneity of municipal conflict-related events through the use of instrumental variables. We find that conflict especially affects children older than eleven, inducing them to drop out of school and enter the labor market too early. We provide evidence that such effects may be generated through higher mortality risks, negative economic shocks and lesser school quality.